Analyses of DC and analog/RF performances for short channel quadruple-gate gate-all-around MOSFET. Issue 8 (August 2015) - Sharma, Dheeraj; Vishvakarma, Santosh Kumar
Abstract In this paper, for the first time, we have analyzed DC characteristics and analog/RF performances for nanowire quadruple-gate (QuaG) gate-all-around (GAA) metal oxide semiconductor field effect transistor (MOSFET), using isomorphic polynomial function for potential distribution. The QuaG GAA MOSFET not only suppresses the short channel effects (SCEs) and offer ideal subthreshold slope (SS), but also is a good candidate for analog/RF device due to its high transconductance (gm) and high cutoff frequency (fT). Therefore, this work would be beneficial for a new generation of RF circuits and systems in a broad range of applications and operating frequencies covering RF spectrum. For this, the developed model is based on the solution of 3D Laplace and Poisson׳s equations for subthreshold and strong inversion regions respectively. The developed potential model has been used to formulate a new model for total gate, drain and source charge. Further, the expression for different capacitance for investigating RF performance is obtained from the developed model. Finally, the developed device electrostatics for QuaG GAA MOSFET have been used for the analysis of analog/RF performance. Different capacitances and analog/RF figures of merit are extracted from small signal frequency (1 MHz) ac device simulation. Whereas technology computer-aided design (TCAD) simulations have been performed by 3D ATLAS, Silvaco International.